2021
DOI: 10.3390/catal11111376
|View full text |Cite
|
Sign up to set email alerts
|

Local Structure of Pd1 Single Sites on the Surface of PdIn Intermetallic Nanoparticles: A Combined DFT and CO-DRIFTS Study

Abstract: Local structure of Pd1 single sites on the surface of Pd1In1 intermetallic nanoparticles supported on α-Al2O3 was investigated by the combination of CO-DRIFTS spectroscopy and DFT. CO-DRIFTS spectra of PdIn/Al2O3 catalyst exhibit only one asymmetric absorption band of linearly adsorbed CO comprising two peaks at 2065 and 2055 cm−1 attributable to CO molecules coordinated to Pd1 sites located at (110) and (111) facets of PdIn nanoparticles. The absence of bridged or hollow-bonded CO bands indicates that multipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…It has been extensively reported that CO is strongly adsorbed on a Pd surface in electrochemical reactions. ,,,,,,, In contrast, DFT calculations reveal that PdIn adsorbs CO weakly as compared to Pd . These literature reports and the above discussion led to the inference that the nanoparticulate IMC PdIn significantly resists being poisoned by CO under the electrochemical reaction conditions.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…It has been extensively reported that CO is strongly adsorbed on a Pd surface in electrochemical reactions. ,,,,,,, In contrast, DFT calculations reveal that PdIn adsorbs CO weakly as compared to Pd . These literature reports and the above discussion led to the inference that the nanoparticulate IMC PdIn significantly resists being poisoned by CO under the electrochemical reaction conditions.…”
Section: Resultsmentioning
confidence: 98%
“…The rest was either {100} In or {111} In , though the {221} facet did not take part in the surface construction. According to this DFT calculation, PdIn particles do not possess triangular Pd ensemble sites, which are the typical surface structures of monometallic Pd and strongly adsorb CO. 48 Electrochemical Performances of Pd/KB and PdIn/KB Electrodes for CO 2 Reduction. Pd/KB and PdIn/KB electrodes were used as the cathodes for CO 2 reduction in an aqueous electrolyte, as shown in Figure 3.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Smirnova et al [26] investigated the local structure of Pd 1 single sites on the surface of relatively large Pd 1 In 1 intermetallic NPs of the size 10-30 nm supported on α-Al 2 O 3 with the combination of experimental and theoretical methods, i.e., CO-DRIFT spectroscopy and DFT calculations. The preparation procedure of the incipient wetness impregnation of α-Al 2 O 3 by an aqueous solution of Pd and In nitrates followed by a reduction with molecular hydrogen was made possible to avoid the formation of monometallic Pd NPs.…”
Section: Introductionmentioning
confidence: 99%